FORMATION OF STUDENTS’ CREATIVE COMPETENCE BY TEACHING LANDSCAPE COMPOSITION - Bakhriyev Ilhomjon Saidazimovich (Web of Journals Publishing, 2024)
This article aims to study the pedagogical and psychological foundations of the process of formation of creative competences by teaching students landscape composition. The article analyzes the theoretical and practical aspects of landscape composition, its role in the development of students’ artistic thinking and creative potential. It is shown that by improving the educational process, it is possible to contribute to not only professional, but also personal development of students. The article is useful for future teachers of fine arts and presents new pedagogical approaches and practical methods for the development of creative competencies.
Keywords: landscape. composition, competence, pedagogical approaches, student, artistic, thinking, creative, development, educational, process, visual arts, Teacher.